2009
DOI: 10.1124/mol.109.058784
|View full text |Cite
|
Sign up to set email alerts
|

Agonists and Allosteric Modulators of the Calcium-Sensing Receptor and Their Therapeutic Applications

Abstract: The calcium-sensing receptor (CaR) belongs to the G proteincoupled receptor superfamily, with a characteristic structure consisting of seven transmembrane helices, an intracellular C-terminal and an extracellular N terminal domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 142 publications
(193 reference statements)
1
78
0
Order By: Relevance
“…(28) Several calcilytics have been reported to reduce the sensitivity of CaSR to extracellular Ca 2þ , and cause a rightward shift of the extracellular Ca 2þ -tointracellular Ca 2þ concentration curve. (29,30) JTT-305 (also known as MK-5442), a short-acting calcilytic, transiently elevates the endogenous PTH secretion, and increases bone mineral density (BMD) in rats. (31) Because activating mutations of CaSR cause ADH, and because calcilytics suppress the enhanced sensitivity of CaSR to extracellular Ca 2þ , there is a possibility that JTT-305/MK-5442 may become a new therapeutic agent to reverse most of the abnormalities in Ca metabolism in ADH patients caused by activating mutations of CaSR.…”
Section: Introductionmentioning
confidence: 99%
“…(28) Several calcilytics have been reported to reduce the sensitivity of CaSR to extracellular Ca 2þ , and cause a rightward shift of the extracellular Ca 2þ -tointracellular Ca 2þ concentration curve. (29,30) JTT-305 (also known as MK-5442), a short-acting calcilytic, transiently elevates the endogenous PTH secretion, and increases bone mineral density (BMD) in rats. (31) Because activating mutations of CaSR cause ADH, and because calcilytics suppress the enhanced sensitivity of CaSR to extracellular Ca 2þ , there is a possibility that JTT-305/MK-5442 may become a new therapeutic agent to reverse most of the abnormalities in Ca metabolism in ADH patients caused by activating mutations of CaSR.…”
Section: Introductionmentioning
confidence: 99%
“…Much has been learned from studies of lingual nutrient detection due to identification of the G protein family, which couples with nutrient-sensitive G protein coupled receptors located in the taste buds on the tongue and in the intestine (26,27). The CaR, a G protein-coupled receptor, is best known and understood for its control of PTH synthesis and secretion in response to changes in Ca, Mg, Sr, and La (17,18). CaRs are distributed along most of the gastrointestinal tract, from the stomach to the large intestine (23,28).…”
Section: Discussionmentioning
confidence: 99%
“…CaRs are distributed along most of the gastrointestinal tract, from the stomach to the large intestine (23,28). The physiologic role of CaRs is the maintenance of constant blood Ca 2 + levels (1.1-1.3 mM) through continuous adjustments of PTH release from the parathyroid chief cells, which are highly sensitive to the slightest changes in extracellular Ca ion concentrations (17,18). In the present study, we showed that Mg, La, or Sr, which are CaR agonists, can partially substitute for dietary Ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, four groups of ligands have been identified for the CaS receptor: the endogenous cations [93] , the L-amino acids (such as L-phenylalanine and L-tryptophan [94] ), the calcimimetics and the calcilytics [95] . Except for the cations, the latter three groups are all allosteric modulators.…”
Section: Cas Receptors -First Clinical Successmentioning
confidence: 99%